Insufficient Knowledge About Primary Health Care Services: Is It the Reason for Not Applying to Family Medicine? - Bayraktar, Mustafa; Mutlu, Muhammet (Cerrahpaşa Medical Journal, 2022)
Objective: The annual number of applications to family health centers in Turkey, which is 3.3, does not meet the Ministry of Health’s target of 4 applications per capita. Due to the necessity of examining the reasons why family medicine is not preferred, this study aimed to investigate the awareness of patients about the health services provided by family health centers. Methods: A cross-sectional, descriptive study was conducted on patients aged 18-75 years who applied to the family health center. They were asked to answer a 3-point Likert scale questionnaire consisting of 24 questions about the health services offered by family health centers. The relationship between the knowledge levels, demographic characteristics, and application rates of the participants was investigated. Results: A total of 165 responses were examined and the mean age of the participants was 35.8 ± 12.8 years, 47.3% were women, 61.8% were married, 59.4% had children, and 23.6% had chronic diseases. The rate of correct answers to the questionnaire was 50.9 ± 23.8. There was a statistically significant association between knowledge levels and women (P < .001), the participants who had children (P = .025), those with chronic diseases (P = .005), and those who applied to family health centers more frequently (P = .019). There were no significant associations in terms of previous applications, age, and marital status. Conclusion: The levels of knowledge and awareness about the healthcare services offered by family health centers were considered to be low. This lack of information may be affecting the application rates of patients. It could be improved through effective activities aimed at disseminating information about and raising awareness of family health centers. Cite this article as: Bayraktar M, Mutlu M. Insufficient knowledge about primary health care services: Is it the reason for not applying to family medicine?. Cerrahpaşa Med J. 2022;46(2):91-96.